Efeito citoprotetor e antioxidante de curcuminoides sintéticos monocarbonilados em macrófagos murinos: envolvimento da via Keap1/Nrf2/ARE - Silva, Mateus Edson da (2025)
Oxidative stress is characterized by the intracellular accumulation of Reactive Oxygen Species (ROS), which actively participates in the development of diseases of inflammatory, cardiovascular, neuropathic, bone, metabolic, infectious nature, among others. Curcumin has been explored for its high antioxidant effect, both as a scavenger and for modulation of signaling pathways, especially the Keap1/Nrf2/ARE pathway. However, its low solubility, stability and pharmacokinetics at physiological pH hinder its clinical use. Recently, a group of synthetic monocarbonyl analogues of curcumin was synthesized, aiming to obtain improved characteristics. Thus, the present study aimed to evaluate the cytoprotective effect of the synthetic monocarbonylated curcuminoids (1E,4E)-1,5- diphenylpenta-1,4-dien-3-one (DBA) and (1E,4E)-1,5-bis(4-methoxyphenyl)penta-1,4-dien-3-one (DBAn) in a model of oxidative stress injury by hydrogen peroxide (H2O2). Initially, molecular docking assays were performed to investigate the theoretical interaction of curcumin (Cur), DBA, and DBAn with both Kelch and Brick-to-Brick (BTB) domains of Keap1. Then, the cytotoxicity and protective effect of curcuminoids on cells exposed to H2O2 were determined by MTT assay in RAW 264.7 murine macrophages. The cell death profile was analyzed by flow cytometry using 7AAD and Annexin V-FITC. Also by cytometry, the accumulation of cytoplasmic ROS was evaluated with DCFH2-DA. Finally, the gene modulation of the Keap1/Nrf2/ARE pathway was evaluated by analyzing the expression of Nrf2 and HO-1 by RT-qPCR. Molecular docking demonstrated that DBA and DBAn interacted with important residues of Kelch domain of Keap1, indicating possible interference with its binding to Nrf2. In the MTT assay, DBA and DBAn showed lower cytotoxicity than Cur in macrophages. Furthermore, they were able to reduce the cytotoxic effect induced by H2O2 in a manner superior to that observed for Cur. Curcuminoids were able to reduce cell death events caused by H2O2, with an increase in viable cells and a reduction in cells labeled with 7AAD and double labeled. Furthermore, Cur, DBA and DBAn reduced the cytoplasmic accumulation of ROS induced by H2O2 at the tested concentrations. Regarding gene expression, treatment with H2O2 increased the relative expression of Nrf2 and HO-1, while curcuminoids caused a reduction on this effect. Thus, the synthetic curcuminoids DBA and DBAn showed cytoprotective and antioxidant effects in a peroxide-induced oxidative stress model, possibly acting as Keap1/Nrf2/ARE pathway modulator. These results may contribute for the development of new targeted antioxidant strategies.